The Relationship between Self-Regulation and Online Learning in a Blended Learning Context - Lynch, Richard; Dembo, Myron (International Review of Research in Open and Distributed Learning, 2004)
This study reviewed the distance education and self-regulation literatures to identify learner self-regulation skills predictive of academic success in a blended education context. Five self-regulatory attributes were judged likely to be predictive of academic performance: intrinsic goal orientation, self-efficacy for learning and performance, time and study environment management, help seeking, and Internet self-efficacy. Verbal ability was used as a control measure. Performance was operationalized as final course grades. Data were collected from 94 students in a blended undergraduate marketing course at a west coast American research university (tier one). Regression analysis revealed that verbal ability and self-efficacy related significantly to performance, together explaining 12 percent of the variance in course grades. Self-efficacy for learning and performance alone accounted for 7 percent of the variance.